Resonance-assisted stabilisation of hydrogen bonds probed by NMR spectroscopy and path integral molecular dynamics - Dračínský, M; Čechová, L; Hodgkinson, P; Procházková, E; Janeba, Z (Chemical communications (Cambridge, England), 2015)
Path integral molecular dynamics and experimental NMR data are used to investigate resonance-assisted hydrogen bonds (RAHBs). When nuclear delocalisation is included in chemical shift calculations, the agreement with experiment is excellent, while static calculations show very poor performance. The results support the concept of RAHB, which has recently been questioned.
Keywords: Hydrogen Bonding; vodíková vazba; simulace molekulární dynamiky; Magnetic Resonance Spectroscopy; Pyrimidines; Nitroso Compounds; Molecular Dynamics Simulation; pyrimidiny; magnetická rezonanční spektroskopie; nitrososloučeniny